Effectiveness in Rural Governance: Influencing Factors and Driving Pathways—Based on 20 Typical Cases of Rural Governance in China - Yu Peng; Xiaobing Peng; Xu Li; Mingyue Lu; Mingze Yin (Land, 2023)
Effective rural governance is the foundation for achieving rural revitalization and promoting the modernization of China’s system and governance capacity in the new era. The elucidation of the influencing factors and driving pathways underlying effective rural governance has significant importance in facilitating the advancement of rural revitalization. Drawing upon the Actor-Network Theory (ANT), this study introduces an analytical framework of “human actor dimension—non-human actor dimension”. The study employs the fuzzy-set Qualitative Comparison Analysis (fsQCA) to explore the effective governance pathways within 20 typical cases of rural governance. The study reveals that a cooperative-based collective economy is a necessary condition for effective governance, while possessing a resource advantage is a core condition. Villager autonomy, local culture, and new technology are marginal conditions for effective governance, while the absence of elite participation fails to promote effective governance. The combination of human variables and resource compacts gives rise to “human actor-resource compacts” and “non-human actor-resource compacts”. The study further elaborates on the efficacious model of rural governance through three multifactor driving pathways: “human actor-non-human actor resource sparse linkage”. The research emphasizes the importance of fortifying rural governance and revitalization through the cultivation of relationships, enhancing government management systems, embracing technological innovation, supporting community economies, and advocating mechanisms that empower rural elites and talent.